Biobatteries: From Microbial Fuel Cells to Biobatteries: Moving toward On‐Demand Micropower Generation for Small‐Scale Single‐Use Applications (Adv. Mater. Technol. 7/2019). Issue 7 (8th July 2019) - Gao, Yang; Mohammadifar, Maedeh; Choi, Seokheun
Abstract : Biobatteries are an excellent power solution for small‐scale, on‐demand, single‐use, and disposable electronics. In article number 1900079, Yang Gao, Maedeh Mohammadifar, and Seokheun Choi present a comprehensive review on small‐scale bacteria‐powered biobatteries and their applications. Potential directions for biobattery research and the associated challenges are discussed to inspire the community and encourage fruitful future research.